1986
DOI: 10.1073/pnas.83.10.3151
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional "silencer" element in rat repetitive sequences associated with the rat insulin 1 gene locus.

Abstract: The enhancer elements from either simian virus 40 or murine sarcoma virus activate the expression of a transfected rat insulin 1 (r11) gene when placed within 2.0 kilobases or less of the rl1 gene cap site. Inclusion of 4.0 kilobases of upstream r11 sequence, however, results in a substantial reduction in the enhancer-dependent insulin gene expression. These observations suggested that a negative transcriptional regulatory element was present between 2.0 and 4.0 kilobases of the r11 sequence. To test this noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(90 citation statements)
references
References 20 publications
1
89
0
Order By: Relevance
“…Surprisingly, activation of the transgenic promoter in two different cell clones was not accompanied by expression of the endogenous Insulin I gene. The explanation for these apparently contradictory results may reside in the fact that the Insulin I gene contains a cis-acting silencer located between −4.0 and −2.0 kb from the transcriptional start site [48] that was not included in the DNA construct used in this study. Since the same promoter region is commonly used for studies on regulation of insulin gene expression, our data caution against interpreting results based only on activation of a similar reporter gene.…”
Section: Discussionmentioning
confidence: 88%
“…Surprisingly, activation of the transgenic promoter in two different cell clones was not accompanied by expression of the endogenous Insulin I gene. The explanation for these apparently contradictory results may reside in the fact that the Insulin I gene contains a cis-acting silencer located between −4.0 and −2.0 kb from the transcriptional start site [48] that was not included in the DNA construct used in this study. Since the same promoter region is commonly used for studies on regulation of insulin gene expression, our data caution against interpreting results based only on activation of a similar reporter gene.…”
Section: Discussionmentioning
confidence: 88%
“…The region between 424 and 439 is included in a somewhat larger domain that has been shown to bind a nuclear protein of unknown identity (13). (22). The distribution of transcriptional silencers throughout the genome on the elements of a repeated gene family may play a role in establishing the default mode of chromatin, namely transcriptional inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, negative regulation of the enhancer is also an important mechanism for the control of heavy-chain expression. Negative-enhancer regulation may be a general mechanism for tissue-specific expression as negativeregulatory elements also have been found that are associated with the insulin 1 gene enhancer (Laimins et al 1986;Nit et al 1986), the B-interferon gene enhancer {Goodbourn et al 1986), and viral enhancers in embryonic stem cells (Gorman et al 1985), and mouse mammary epithelial cells (Langer and Ostrowski 1988).…”
Section: Models For Enhancer Repressionmentioning
confidence: 99%